Integrated multi‐omics analysis uncovers roles of mdm‐miR164b‐MdORE1 in strigolactone‐mediated inhibition of adventitious root formation in apple. (19th September 2022) - Fan, Xingqiang; Li, Hui; Guo, Yushuang; Sun, Haochen; Wang, Shiyao; Qi, Qi; Jiang, Xiangning; Wang, Yi; Xu, Xuefeng; Qiu, Changpeng; Li, Wei; Han, Zhenhai
Abstract: Apple is one of the most important fruit crops in temperate regions and largely relies on cutting propagation. Adventitious root formation is crucial for the success of cutting propagation. Strigolactones have been reported to function in rooting of woody plants. In this study, we determined that strigolactones have inhibitory effects on adventitious root formation in apple. Transcriptome analysis identified 12 051 differentially expressed genes over the course of adventitious root initiation, with functions related to organogenesis, cell wall biogenesis or plant development. Further analysis indicated that strigolactones might inhibit adventitious root formation through repressing two core hub genes, MdLAC3 and MdORE1 . Combining small RNA and degradome sequencing, as well as dual‐luciferase sensor assays, we identified and validated three negatively correlated miRNA–mRNA pairs, including mdm‐miR397– MdLAC3 and mdm‐miR164a/b– MdORE1 . Overexpression of mdm‐miR164b and silencing MdORE1 exhibited enhanced adventitious root formation in tobacco and apple, respectively. Finally, we verified the role of mdm‐miR164b– MdORE1 in strigolactone‐mediated repression of rooting ability. Overall, the identified comprehensive regulatory network in apple not only provides insight into strigolactone‐mediated adventitious root formation in other woody plants, but also points to a potential strategy for genetic improvement of rooting capacity in woody plants. Summary statement: The effects of strigolactones on adventitious root formation have been rarely reported, especially in woody plants. In this study, we have demonstrated the inhibitory roles of strigolactones on adventitious root formation in apple, proposed a comprehensive regulatory network, and identified core genes for strigolactone‐mediated inhibition of rooting ability.